Blooket: A Teacher's Toolkit for Improving Students' Reading Comprehension and Vocabulary Mastery - Muharomah, Siti Anugrah; Hidayani, Selnistia; Perdana, Purnama Rika (International Journal of English Education and Linguistics (IJoEEL), 2025)
Vocabulary mastery and reading comprehension are difficult for certain student. This conventional strategy has many drawbacks. Therefore, technology plays an important role in the scope of teaching and learning English as a Foreign Language (EFL). Engaging students' habits with their gadgets, particularly in the "Blooket.com" game-based learning strategy is a new way to help improve students' vocabulary mastery and reading comprehension. This study aims to use of Blooket as a game-based learning tool impact students' reading comprehension and vocabulary mastery? The qualitative study will be conducted as a study-based design and focus on the teacher's perception of playing the Blooket game. A total of 10 junior high school teachers in the city of Serang who had used the Blooket game in learning were involved as research subjects. Teachers are given questionnaires using Google Forms, and information is collected in the form of numbers and percentages, which are then interpreted in qualitative sentences. Based on a survey of teachers regarding the use of Blooket in the learning process, it can be concluded that Blooket has great potential as a flexible and attractive teaching tool for students. The majority of teachers agree that Blooket can help track student progress, measure comprehension of complex texts, and introduce new vocabulary effectively.